Kinetics of chemokine-glycosaminoglycan interactions control neutrophil migration into the airspaces of the lungs - Tanino, Y.; Coombe, Deirdre; Gill, S.; Kett, Warren; Kajikawa, O.; Proudfoot, A.; Wells, T.; Parks, W.; Wight, T.; Martin, T.; Frevert, C. (American Association of Immunologists, 2010)
Chemokine–glycosaminoglycan (GAG) interactions are thought to result in the formation of tissue-bound chemokine gradients. We hypothesized that the binding of chemokines to GAGs would increase neutrophil migration toward CXC chemokines instilled into lungs of mice. To test this hypothesis we compared neutrophil migration toward recombinant human CXCL8 (rhCXCL8) and two mutant forms of CXCL8, which do not bind to heparin immobilized on a sensor chip. Unexpectedly, when instilled into the lungs of mice the CXCL8 mutants recruited more neutrophils than rhCXCL8. The CXCL8 mutants appeared in plasma at significantly higher concentrations and diffused more rapidly across an extracellular matrix in vitro. A comparison of the murine CXC chemokines, KC and MIP-2, revealed that KC was more effective in recruiting neutrophils into the lungs than MIP-2. KC appeared in plasma at significantly higher concentrations and diffused more rapidly across an extracellular matrix in vitro than MIP-2. In kinetic binding studies, KC, MIP-2, and rhCXCL8 bound heparin differently, with KC associating and dissociating more rapidly from immobilized heparin than the other chemokines. These data suggest that the kinetics of chemokine–GAG interactions contributes to chemokine function in tissues. In the lungs, it appears that chemokines, such as CXCL8 or MIP-2, which associate and disassociate slowly from GAGs, form gradients relatively slowly compared with chemokines that either bind GAGs poorly or interact with rapid kinetics. Thus, different types of chemokine gradients may form during an inflammatory response. This suggests a new model, whereby GAGs control the spatiotemporal formation of chemokine gradients and neutrophil migration in tissue.